Penerapan Arsitektur Enterprise pada Sekolah Tinggi Ilmu Ekonomi STIE YPPI Rembang - Riki Rizki Nur Shidiq; Ilyas Nuryasin; Wildan Suharso (Universitas Muhammadiyah Malang, 2023)
STIE YPPI Rembang School of Economics is one of the high schools located in the Rembang area, Central Java. At the present time, with the resources owned by the STIE YPPI Rembang, data management is still managed manually and has not been integrated with one another. Therefore, it is necessary to research the development of information systems that are integrated with each other in order to produce an enterprise architecture blueprint. Research conducted at the Rembang School of Economics uses the Enterprise Architecture Planning methodology. The results of the research conducted at the STIE Rembang is a blueprint or enterprise architecture which is a strategic plan for the information system of the STIE YPPI Rembang. This enterprise architecture can later be used as the foundation for the STIE YPPI Rembang in making a policy and creating an academic information system that is connected to one another. From the identification of the enterprise, it produces 12 business process models 42 entities, and 12 candidate applications.